DECODING SPEECH ACTS IN "RAMBO LAST BLOOD" MOVIE - I Putu Arde Waisnawa, arde (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Effective communication is a crucial skill for human interaction in daily life, with language serving as a primary tool. The study of speech acts contributes significantly to our understanding of language. This research specifically seeks to identify various types of illocutionary acts and discern their intended meanings. The dataset for this study is derived from the movie "Rambo Last Blood”. The data were collected by observation method and note taking technique by classifying data based on types of illocutionary acts the collected data were analyzed by descriptive qualitative method by using theory proposed by Yule (1996) and Leech (1981) to analyze the types and the intended meaning of illocutionary acts uttered by all characters in Rambo Last Blood movie. The results indicate the presence of all illocutionary act types in the movie, including representative, directive, commissive, expressive, and declarative acts. The statements convey meanings that are both explicit and implicit, with the hidden significance becoming apparent through an understanding of the contextual situation in the story.